Analysis of Student Errors in Solving Problems on the Matrix - Fatwiyati Sholikhah Cahyaningrum; Afif Afghohani (Journal of Medives: Journal of Mathematics Education IKIP Veteran Semarang)
This research aims to identify mistakes made by students in solving essay questions of the material matrix. This research method applies descriptive qualitative research. The subjects of this study were students in grades XI BDP of SMK PGRI Sukoharjo in the academic year 2020/2023, with a total of 40 students in class. Data collection techniques used answers to written test description questions for Class XI BDP students which consisted of five questions. The conclusions obtained from the results of the analysis based on Newman’s stages are (1) reading error; (2) comprehension error; (3) transformation error; (4) process skill error; (5) encoding error. Student errors are caused by several factors, namely: students are in a hurry, are not careful in reading questions, cannot mention what is known in full, are unable to identify the correct method, lack knowledge of symbols, use inappropriate steps, errors in calculations, and unable to write the notation correctly